Alcohol Consumption and Cardiovascular Outcomes in Patients With Nonalcoholic Fatty Liver Disease: A Population‐Based Cohort Study. Issue 3 (20th December 2021) - Janjua, Malik; Knuiman, Matthew; Divitini, Mark; McQuillan, Brendan; Olynyk, John K.; Jeffrey, Gary P.; Adams, Leon A.
Abstract : Low‐level alcohol consumption is associated with reduced cardiovascular disease (CVD) in the general population. It is unclear whether this association is seen in patients with nonalcoholic fatty liver disease (NAFLD) who have an increased risk of CVD. We examined the association between alcohol consumption and CVD‐related outcomes in subjects with NAFLD from a general population cohort. Subjects participating in the 1994‐1995 Busselton Health survey underwent clinical and biochemical assessment. NAFLD was identified using the Fatty Liver Index of >60, and alcohol consumption quantified using a validated questionnaire. CVD hospitalizations and death during the ensuing 20 years were ascertained using the Western Australian data linkage system. A total of 659 of 4, 843 patients were diagnosed with NAFLD. The average standard drinks per week was 8.0 for men and 4.0 for women. Men consuming 8‐21 drinks per week had a 38% (hazard ratio [HR] 0.62, 95% confidence interval [CI] 0.43‐0.90) lower risk of CVD hospitalization as compared with men consuming 1‐7 drinks per week. With both men and women combined, consumption of 8‐21 drinks per week was associated with a 32% (HR 0.68, 95% CI 0.49‐0.93) reduction in CVD hospitalization in minimally adjusted and 29% (HR 0.71, 95% CI 0.51‐0.99) in fully adjusted models. No protective association was observed with binge drinking. There was no association between alcohol consumption and CVD death. Conclusion: Low to moderate alcohol consumption is associated with fewer CVD hospitalizations but not CVD death in subjects with NAFLD.